Plasma protein biomarkers of Plasmodium falciparum infection in pregnant women: a high-throughput proteomics study - Bernard N. Kanoi; Harrison Waweru; Francis M. Kobia; Joseph Mukala; Peter Kirira; Dominic Mogere; Radiosa Gallini; Mikael Åberg; Manu Vatish; Jesse Gitaka; Masood Kamali-Moghaddam (Frontiers in Cellular and Infection Microbiology)
IntroductionPregnant women in sub-Saharan Africa face heightened susceptibility to Plasmodium falciparum malaria, with placental sequestration driving adverse outcomes. The infection may lead to pregnancy-associated malaria (PAM) because of the sequestration of Plasmodium falciparum-infected erythrocytes in the placental intervillous space. Although there are several tools for diagnosing malaria infection during pregnancy, including blood smear microscopic examination, rapid diagnostic tests, and PCR, there are no tools for detecting placental infection and, by extension, any dysfunction associated with PAM. Thus, PAM, specifically placental infection, can only be confirmed via postnatal placental histopathology. Therefore, there is an urgent need for specific plasma biomarkers of PAM.MethodsHere, we used the high throughput proximity extension assay to screen plasma from malaria-exposed pregnant women for differentially expressed proteins that may serve as candidate biomarkers of Plasmodium falciparum infection during pregnancy, with future potential to inform diagnosis of PAM or adverse malaria outcomes. Such biomarkers may also elucidate the pathophysiology of PAM.ResultsUsing proximity extension assay (PEA), we identified elevated IgG Fc receptor IIb (FCGR2B) and heme oxygenase-1 (HO-1) in malaria-positive pregnancies, while neurturin (NRTN) and IL-20 were downregulated.DiscussionIL-20 emerged as a top candidate biomarker, warranting validation in large cohorts with placental histopathology.